Heavy metals binding properties of esterified lemon - Arslanoğlu, Hasan; Altundoğan, Hamdi Soner; Tümen, Fikret (My University, 2009)
Sorption of Cd2+, Cr3+, Cu2+, Ni2+, Pb2+ and Zn2+ onto a carboxyl groups-rich material prepared from lemon was investigated in batch systems. The results revealed that the sorption is highly pH dependent. Sorption kinetic data indicated that the equilibrium was achieved in the range of 30–240 min for different metal ions and sorption kinetics followed the pseudo-second-order model for all metals studied. Relative sorption rate of various metal cations was found to be in the general order of Ni2+ > Cd2+ > Cu2+ > Pb2+ > Zn2+ > Cr3+. The binding characteristics of the sorbent for heavy metal ions were analyzed under various conditions and isotherm data was accurately fitted to the Langmuir equation. The metal binding capacity order calculated from Langmuir isotherm was Pb2+ > Cu2+ > Ni2+ > Cd2+ > Zn2+ > Cr3+. The mean free energy of metal sorption process calculated from Dubinin–Radushkevich parameter and the Polanyi potential was found to be in the range of 8–11 kJ mol?1 for the metals studied showing that the main mechanism governing the sorption process seems to be ion exchange. The basic thermodynamic parameters of metals ion sorption process were calculated by using the Langmuir constants obtained from equilibration study. The ?G° and ?H° values for metals ion sorption on the lemon sorbent showed the process to be spontaneous and exothermic in nature. Relatively low ?H° values revealed that physical adsorption significantly contributed to the mechanism.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Lemon; Heavy metal; Sorption characteristics; Kinetics; Thermodynamics